The spirit of Aid - Mhd. Sarif, Suhaimi; Zainudin, Dolhadi; Ismail, Yusof; Firmansah, Yayan; Yahya, Rohaziah (IIUM Press, 2025)
This case study explores the dynamic interplay between the National Union of Workers (NUW) and the Federation of Commercial Financiers (FCF) in the financial sector in Malaysia with the focus on the events surrounding the “Festival Aid” initiative during the tumultuous post-pandemic period. Tracing the roots of both organisations to Malaysia’s economic transformation in the 1960s, the case study argued that the respective missions, organisational structures, and the evolution of collective bargaining practices were shaped by decades of partnership and occasional conflict. The case study utilised narrative and observation to highlight the arguments arising from FCF’s unilateral withdrawal of Festival Aid after its initial success, as well as the subsequent legal and moral challenges and the conciliation process that ensued. The analysis foregrounds the adoption of MADANI values—sustainability, prosperity, innovation, respect, trust, and care & compassion—showing how both employers and unions grappled with questions of technical obligations versus moral stewardship, the role of dialogue and trust in industrial relations, and the transformation of adversarial bargaining into a model for inclusive, responsible social partnership. The case study concludes with lessons for policymakers, employers, and unionists seeking to harmonise economic resilience with social justice in a rapidly evolving, multicultural society.